2016
DOI: 10.1016/j.tox.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exposure time on toxicity—An overview

Abstract: Data on toxicity of chemicals is usually reported as the LD50, or LC50, with the exposure time from experimental testing in the laboratory reported. But the exposure time is not considered to be a quantifiable variable which can be used to evaluate its importance in expressed toxicity, often described in general terms such as acute, chronic and so on. For the last hundred years Habers Rule has been successfully used to extrapolate from reported exposure times to other exposure times which may be needed for set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 12 publications
2
25
0
15
Order By: Relevance
“…[14]) and an exposure time dependence of toxicity has also been described for aquatic organisms (e.g. [2,10,12]). Hence, the exposure time dependence is an important and so far often neglected aspect of the regulatory ecotoxicological risk assessment, in particular for the long-term assessment.…”
Section: Introductionmentioning
confidence: 99%
“…[14]) and an exposure time dependence of toxicity has also been described for aquatic organisms (e.g. [2,10,12]). Hence, the exposure time dependence is an important and so far often neglected aspect of the regulatory ecotoxicological risk assessment, in particular for the long-term assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also reached the same conclusion while studying the toxic effects of organic pollutants to fish [12]. The transfer of compounds from water to fish is the first step in the development of toxic effects [26].…”
Section: Interpretation Of the Ec 50 Reduction Over Time Based On Thementioning
confidence: 58%
“…It was noted that the relationship between natural logarithm of exposure time (lnET 50 ) and EC 50 for zebrafish was linear. The RLE model allows the normal life expectancy (NLT) to be calculated from the toxicity data [12]. In previous study, the reported NLT and calculated NLT obtained were in general agreement [5].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations